An Arterial Spin Labeling MRI Perfusion Study of Migraine without Aura Attacks - Gil-Gouveia, Raquel; Pinto, Joana; Figueiredo, Patricia; Vilela, Pedro Ferro; Martins, Isabel Pavão (Frontiers in Neurology, 2017)
Background: Studies of brain perfusion during migraine without aura attacks have inconsistent results. Methods: Arterial Spin Labeling (ASL) MRI, a non-invasive quantitative perfusion technique, was used to prospectively study a spontaneous untreated migraine without aura attack and a headache-free period. Image analysis used FSL and MATLAB software; Group analysis used permutation methods for perfusion differences between sessions. Results: Thirteen women (age 35.7) were scanned during an attack of an average intensity of 6.8 (on 0-10 Visual Analogue Scale, VAS) and 16 hours duration. No global or regional perfusion differences were identified comparing migraine and migraine-free sessions. Discussion: Our findings suggest that the painful phase of migraine without aura attacks is not associated with brain perfusion abnormalities